TMIC-37. SINGLE-CELL CHARACTERIZATION OF THE IMMUNE LANDSCAPE OF EXTREME LONG-TERM SURVIVORS WITH MALIGNANT GLIOMA. (14th November 2022) - Decraene, Brecht; Antoranz, Asier; Verbeke, Tatjana; Vanmechelen, Maxime; Nazari, Pouya; Solie, Lien; Dubroja, Nikolina; Derweduwe, Marleen; Spans, Lien; Bempt, Isabelle Vanden; Sciot, Raf; De Smet, Frederik; et al.
Abstract: Glioblastoma Multiforme (GBM) remains the most common malignant primary brain tumor with a dismal prognosis that rarely exceeds beyond two years despite extensive therapy, which consists of maximal safe surgical resection, radiotherapy and/or chemotherapy. Recently, it has become clear that GBM is not one homogeneous entity and that both intra-and intertumoral heterogeneity contribute significantly to differences in tumoral behavior which may consequently be responsible for differences in survival. Strikingly and despite its dismal prognosis, small fractions of GBM patients seem to display extreme extended survival compared to the large majority of patients. The underlying mechanisms for this peculiarity remain largely unknown however, even though emerging data suggest that both cancer cell-autonomous and microenvironmental factors and their interplay probably play an important role. We used high-dimensional, multiplexed immunohistochemistry to spatially, and cytometry by time-of-flight to quantitively, characterize the cell constitution and interactions within the tumor microenvironment (TME) in 21 extreme long-term survivors (living over 10 year) and 42 deeply matched controls and therefore short-term survivors (living under 1.5 year) on a single cell level. For all tumors (epi)genetic data was also collected. We identified a high level of both inter-and intrapatient heterogeneity defined by several distinct tumoral niches, as well as described interactions within these niches and with the surrounding infiltrating immune cells of the TME in GBM. Finally, by linking patient characteristics with the heterogeneous immune composition we are able to create an immune stratification that can be linked to patient survival in GBM. Therefore, this study is an essential initial step towards strategies to alter the TME in a favorable way with a personalized modulation strategy.